Distribution of Manganese-Substituted Magnetites in Dusts from Taranto, Italy. (30th September 2020) - Peli, M; Bostick, B C; Barontini, S; Placidi, D; Giorgino, A; Ranzi, R; Smith, D R; Conversano, M; Lucchini, R G
Abstract: Elevated exposure to manganese (Mn) in environmental dusts and airborne particulates, particular from ferromanganese alloy steel production and metal working, is associated with a number of negative health outcomes, including Parkinsonism and other nervous system diseases. Manganese contamination and exposure from industrial sources is difficult to identify or quantify, as manganese is naturally abundant in the environment, and means to distinctly identify or fingerprint Mn arising from different industrial and environmental sources are limited. Here, the chemical and mineralogical properties of Mn in dusts from an active steel production facility in Taranto, Italy, were compared with those of indoor and outdoor deposited dust samples and surface soils collected in a series of schools in the nearby town. X-ray absorption spectroscopy revealed distinct chemical forms of Mn in industrial sources from those in typical background soils. Manganese ore from the facility contained abundant Mn(III, IV) oxides, while Mn-substituted magnetites were the most abundant mineral phase in dusts found in areas of the plant where metal was produced or combustion occurred. All school dusts were primarily composed of Mn-substituted magnetites, while most of the soils contained abundant manganese(IV) oxides. Source apportionment of Mn in regional dust and soil samples was estimated using linear combination fitting with representative industrial source materials. Manganese in dusts from the Taranto area community adjacent to the plant was derived primarily from industrially-sourced dusts produced during high temperature coke or steel production rather than re-suspended local soils or ore source material. Soils contained smaller proportion of industrially-derived Mn and are distinct from dusts, indicating that soil is a minor contributor of dust Mn in this area. Key messages: Manganese speciation gives useful information in investigating Mn toxicology to humans in urban areas. Manganese-substituted magnetites may represent the target compound useful to distinguish toxic and non-toxic Mn-containing elements.